hw01_problem5 - d - ((a+b)/c) + (a+d)^2/sqrt(abs(a*b*c)) %...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
% a. 2.6365e+003 (7/3)^2*4^3*18-(6^7/(9^3-652)) % b. 0.2846 cos(5*pi/6)*(sin(7*pi/8))^2+(tan(pi*log(8)/6)/(sqrt(7)+2)) % c. 82.2946 a = -18.2 b = 6.42 c = a/b d = 0.5*(c*b+2*a)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: d - ((a+b)/c) + (a+d)^2/sqrt(abs(a*b*c)) % d. -1.1995 a = -18.2 b = 6.42 c = a/b d = 0.5*(c*b+2*a) log((c-d)*(b-a))+(a+b+c+d)/(a-b-c-d)...
View Full Document

This note was uploaded on 02/12/2012 for the course ENGR 126 taught by Professor Oakes during the Fall '08 term at Purdue University-West Lafayette.

Ask a homework question - tutors are online